Biomass-based hard carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202610960442.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
这一限制导致了两个关键问题:(1)这种电压分布将很大一部分容量限制在低电压范围内,这降低了整个电池的能量密度,不利于高倍率充放电;(2)斜坡区以表面吸附和缺陷储钠为主,伴随严重的副反应与不可逆钠消耗,导致首圈库伦效率偏低,限制了其在实际全电池体系中的应用
1. 本发明通过低温预氧化工艺,实现了前驱体的分子级化学交联,将石墨化纳米带原位嵌入无定形硬碳基质中,有效抑制了碳微晶的无序塌陷,使所得硬碳在保持较大层间距的同时,呈现出更为连续和有序的伪石墨相结构,显著提升了钠离子的快速传输能力;
Smart Images

Figure CN123017962A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a biomass-based hard carbon anode material, its preparation method, and its application. Background Technology
[0002] In sodium-ion batteries, the performance of the anode material directly determines the battery's energy density and rate performance. Since graphite is difficult to reversibly store sodium, hard carbon, with its larger interlayer spacing, abundant defect structure, and multiple sodium storage mechanisms, exhibits higher specific capacity and better cycle stability, making it one of the most promising anode materials for sodium-ion batteries. Compared to fossil-based and polymer-based hard carbon, biomass-based hard carbon has a lower synthesis cost and greater sustainability, which is key to promoting the practical application of sodium-ion batteries.
[0003] Currently, commercially available, electrochemically stable biomass-based hard carbon anodes have limited specific capacities (typically 200-300 mAh·g). -1 Most of the capacity is located in the slope region of the voltage distribution. This limitation leads to two key problems: (1) This voltage distribution restricts a large part of the capacity to the low voltage range, which reduces the energy density of the entire battery and is not conducive to high-rate charging and discharging; (2) The slope region is mainly composed of surface adsorption and defect sodium storage, accompanied by serious side reactions and irreversible sodium consumption, resulting in low coulombic efficiency in the first cycle, which limits its application in actual full battery systems.
[0004] Existing technologies attempt to improve the sodium-ion diffusion kinetics of hard carbon through pore formation and heteroelement doping to significantly optimize its rate performance. However, these methods often inevitably introduce more defect sites and surface-active groups, leading to increased side reactions and irreversible sodium consumption, thus further reducing the initial coulombic efficiency. Therefore, developing a biomass-based hard carbon anode material that can achieve both high initial efficiency and high rate performance is crucial for promoting the practical application of sodium-ion batteries. Summary of the Invention
[0005] This invention discloses a biomass-based hard carbon anode material, its preparation method, and its application. First, pseudo-graphitized nanoribbons are in-situ embedded into an amorphous hard carbon matrix via chemical crosslinking, promoting sodium ion diffusion kinetics in the low potential region (<0.1 V vs Na+ / Na). Then, a low-cost nano-carbon coating is used to passivate defects on the hard carbon surface, improving the initial coulombic efficiency of the hard carbon anode. Finally, when used as an anode material for sodium-ion batteries, this hard carbon material exhibits excellent rate performance and initial coulombic efficiency.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh the precursor and crosslinking agent and add them to the three-dimensional mixer. Mix them to obtain the precursor mixture. S2. Place the precursor mixture obtained in S1 in a muffle furnace and calcine it to obtain a pre-oxidized material. S3. The pre-oxidized material obtained in S2 is calcined in a tube furnace to obtain a high-temperature carbonized material. S4. Weigh the high-temperature carbonized material obtained in S2 and the coating agent, add them to the three-dimensional mixer, mix, and obtain the coating material; S5. The coating material obtained in S4 is calcined in a tube furnace to obtain a biomass-based hard carbon anode material with high rate of return and high first-time efficiency.
[0007] Furthermore, the precursor in step S1 is a biomass raw material with a cellulose content greater than 35%, and the crosslinking agent is a petroleum-based organic waste. By using the above-mentioned biomass raw material in combination with the corresponding crosslinking agent, the hard carbon material obtained after the crosslinking reaction has good crosslinking skeleton stability and suitable density, making it more suitable as a negative electrode material for sodium-ion batteries.
[0008] Furthermore, the precursor is one or more of bamboo, reed, sugarcane bagasse, and corn cob, and the crosslinking agent is one or more of asphalt, polyethylene, and epoxy resin. The mass ratio of the precursor to the crosslinking agent is 1:0.01-0.1. For example, the mass ratio of the precursor to the crosslinking agent is 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, or a range between any two of the above numbers, such as 1:0.02-0.1, 1:0.03-0.1, 1:0.05-0.1, 1:0.07-0.1, 1:0.03-0.08. By further selecting the types of precursors and crosslinking agents, and combining them with appropriate raw material ratios, the hard carbon materials obtained after the crosslinking reaction have better crosslinking skeleton stability and more suitable density, making them more suitable as a negative electrode material for sodium-ion batteries.
[0009] Further, the mixing speed mentioned in step S1 is 300-500 rpm, and the mixing time is 4-6 hours. For example, the mixing speed can be 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm, 350 rpm, 360 rpm, 370 rpm, 380 rpm, 390 rpm, 400 rpm, 410 rpm, 420 rpm, 430 rpm, 440 rpm, 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm, or 500 rpm, or a range between any two of the above numbers, such as 310-500 rpm, 330-500 rpm, 350-500 rpm, 380-500 rpm, 400-500 rpm, 420-500 rpm. The mixing times are 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.3h, 5.5h, 5.7h, 5.9h, 6.0h, or any range between any two of the above numbers, such as 4.2-6h, 4.4-6h, 4.6-6h, 4.8-6h, 5.2-6h, 5.7-6h, 4.4-5.7h, 4.6-5.5h, 4.8-5.0h. By adopting the above process conditions, it can be ensured that the precursor and crosslinking agent are mixed evenly and in full contact, which is beneficial to the subsequent crosslinking reaction.
[0010] Furthermore, the calcination atmosphere in step S2 is air, and the heating rate is 1-3℃ / min. -1 The calcination temperature is 300-400℃, the calcination time is 2-4 hours, and exemplarily, the heating rate is 1℃ / min. -1 2℃ min -1 3℃ min -1 Or, a range between any two of the above numbers, for example, 1-2℃ min. -1 2-3℃ min -1The calcination temperatures are 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, or any range between any two of the above numbers, such as 310-400℃, 320-400℃, 350-400℃, 360-400℃, 380-400℃, 300-380℃, 320-380℃, 340-360℃, etc., and the calcination times are 2.0h, 2.2h, 2. The time intervals can be 4h, 2.6h, 2.8h, 3.0h, 3.3h, 3.5h, 3.7h, 3.9h, 4.0h, or any range between any two of the above numbers, such as 2.2-4h, 2.4-4h, 2.6-4h, 2.8-4h, 3.2-4h, 3.7-4h, 2.4-3.7h, 2.6-3.5h, 2.8-3.0h, etc. By adopting the above process conditions, the cross-linking reaction can be fully carried out, resulting in a suitable framework structure for sodium-ion batteries.
[0011] Furthermore, the calcination atmosphere in step S3 is a nitrogen atmosphere, and the calcination is divided into two steps. The two-step calcination can make the combustion more complete, the carbon yield higher, and the pores more uniform.
[0012] Furthermore, the heating rate is 4-6℃·min -1 The first calcination step is performed at a temperature of 600-800℃ for 3-5 hours, and the second calcination step is performed at a temperature of 1300-1500℃ for 3-5 hours. For example, the heating rate is 4℃ / min. -1 5℃ min -1 6℃ min -1 Or, a range between any two of the above numbers, for example, 4-5℃ min. -1 5-6℃min -1The calcination temperature for the first step is 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, or a range between any two of the above numbers, such as 610-800℃, 620-800℃, 650-800℃, 660-800℃, 680-780℃, 600-780℃, 620-720℃. The calcination temperatures are 0℃, 640-760℃, etc., with calcination times of 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.3h, 4.5h, 4.7h, 4.9h, 5.0h, or any range between any two of the above numbers, such as 3.2-5h, 3.4-5h, 3.6-5h, 3.8-5h, 4.2-5h, 4.7-5h, 4.4-4.7h, 3.6-4.5h, 3.8-4.0h, etc. The calcination temperature in the second step is 1300℃, 1310℃, 1320℃, 1330℃, etc. 1340℃, 1350℃, 1360℃, 1370℃, 1380℃, 1390℃, 1400℃, 1410℃, 1420℃, 1430℃, 1440℃, 1450℃, 1460℃, 1470℃, 1480℃, 1490℃, 1500℃, or any range between any two of the above numbers, such as 1310-1500℃, 1320-1500℃, 1350-1500℃, 1360-1500℃, 1380-1480℃, 1300-1480℃, 1320-1420℃. The calcination temperatures can be 0℃, 1340-1460℃, etc., with calcination times of 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.3h, 4.5h, 4.7h, 4.9h, 5.0h, or any range between any two of the above numbers, such as 3.2-5h, 3.4-5h, 3.6-5h, 3.8-5h, 4.2-5h, 4.7-5h, 4.4-4.7h, 3.6-4.5h, 3.8-4.0h, etc. By adopting the above process conditions, more complete combustion, high carbon yield, and uniform pore size can be ensured.
[0013] Furthermore, the coating agent mentioned in step S4 is a polysaccharide. The polysaccharide coats the high-temperature carbonized material more uniformly and densely, and the contact is closer. The structure obtained after subsequent calcination can effectively passivate the highly active defects and oxygen-containing functional groups on the hard carbon surface, significantly reduce the side reactions of the electrolyte during the first charge and discharge process, and improve the first coulomb effect of the battery. Furthermore, the coating agent is one or more of glucose, sucrose, and chitosan. By using the above raw materials, structural defects can be reduced more effectively and the performance of the negative electrode can be improved.
[0014] Further, in step S4, the mass ratio of the high-temperature carbonizing material to the coating agent is 1:0.05-0.1, the mixing speed is 300-500 rpm, and the mixing time is 4-6 hours. For example, the mass ratio of the high-temperature carbonizing material to the coating agent is 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, or a range between any two of the above values, such as 1:0.05-0.09, 1:0.06-0.09, 1:0.05-0.09, 1:0.09-0.09. 7:0.09, 1:0.08-0.09, 1:0.06-0.08, etc., with mixing speeds of 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm, 410rpm, 420rpm, 430rpm, 440rpm, 450rpm, 460rpm, 470rpm, and 480rpm. 490 rpm, 500 rpm, or any range between any two of the above numbers, such as 310-500 rpm, 330-500 rpm, 350-500 rpm, 380-500 rpm, 400-500 rpm, 420-500 rpm, 450-500 rpm, 310-480 rpm, 350-450 rpm, 380-420 rpm, etc.; the mixing time is 4.0 h, 4.2 h, 4.4 h, 4.6 h. h, 4.8h, 5.0h, 5.3h, 5.5h, 5.7h, 5.9h, 6.0h, or any range between any two of the above numbers, such as 4.2-6h, 4.4-6h, 4.6-6h, 4.8-6h, 5.2-6h, 5.7-6h, 4.4-5.7h, 4.6-5.5h, 4.8-5.0h. By adopting the above process conditions, the high-temperature carbonized material and the coating agent can be mixed evenly and fully contacted, which is beneficial to the subsequent coating reaction.
[0015] Furthermore, the calcination atmosphere in step S5 is a nitrogen atmosphere, and the heating rate is 1-3℃·min. -1 The calcination temperature is 300-500℃, the calcination time is 2-4 hours, and the heating rate is 1℃·min. -1 2℃·min -1 3℃·min -1 Or, a range between any two of the above numbers, for example, 1-2℃·min -1 2-3℃·min -1The calcination temperatures are 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, or any range between any two of the above numbers, such as 310-400℃, 320-400℃, 350-400℃, 360-400℃, 380-400℃, 300-380℃, 320-380℃, 340-360℃, etc., and the calcination times are 2.0h, 2.2h, 2.4h, etc. h, 2.6h, 2.8h, 3.0h, 3.3h, 3.5h, 3.7h, 3.9h, 4.0h, or any range between any two of the above numbers, such as 2.2-4h, 2.4-4h, 2.6-4h, 2.8-4h, 3.2-4h, 3.7-4h, 2.4-3.7h, 2.6-3.5h, 2.8-3.0h, etc. By adopting the above process conditions, it is possible to ensure that the coating agent burns completely, has a good carbonization effect, and obtains a suitable structure for sodium-ion batteries.
[0016] On the other hand, the present invention also provides a biomass-based hard carbon anode material, which is prepared by any of the preparation methods described above.
[0017] Meanwhile, the present invention also provides an application of a biomass-based hard carbon anode material, namely, the application of the hard carbon anode material prepared by any of the above-described preparation methods in the anode material of sodium-ion batteries.
[0018] Compared with existing technologies, the biomass-based hard carbon anode material provided by this invention has the following technical advantages: 1. This invention achieves molecular-level chemical cross-linking of the precursor through a low-temperature pre-oxidation process, embedding graphitized nanoribbons in situ into an amorphous hard carbon matrix, effectively suppressing the disordered collapse of carbon microcrystals, so that the resulting hard carbon exhibits a more continuous and ordered pseudo-graphite phase structure while maintaining a large interlayer spacing, significantly improving the rapid transport capability of sodium ions. 2. This invention uses a secondary coating and low-temperature carbonization process to make the coated carbon layer uniformly and densely cover the surface of hard carbon particles, effectively passivating the highly active defects and oxygen-containing functional groups on the surface of hard carbon, significantly reducing the side reactions of the electrolyte during the first charge and discharge process, and improving the first coulomb effect of the battery. 3. This invention overcomes two key technical bottlenecks—poor rate performance and low initial coulombic efficiency—in hard carbon anode materials through a synergistic modification strategy of bulk crosslinking and surface coating. Furthermore, by selecting specific raw materials, it ensures both excellent product performance and wide availability, low cost, and strong process controllability, providing a practical and feasible technical path for the large-scale, low-cost manufacturing of high-performance hard carbon anode materials. Attached Figure Description
[0019] Figure 1 The graph shows a comparison of the specific capacity and initial coulombic efficiency of the hard carbon anode materials prepared in Example 1 and Comparative Examples 1-3.
[0020] Figure 2 The graph shows a comparison of the specific capacity and initial coulombic efficiency of the hard carbon anode materials prepared in Examples 1-6.
[0021] Figure 3 The first charge-discharge curves of hard carbon materials as the negative electrode of sodium-ion half-cells in Examples 1 and 1-3 are shown.
[0022] Figure 4 As in Example 1 and Comparative Examples 1-3, hard carbon material was used as the anode of a sodium-ion half-cell at 150 mA·g. -1 Cyclic performance diagram after 100 cycles at current density. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.
[0025] The preparation method and characterization in the following examples are based on... Figure 1-4 Unless otherwise specified, all methods are conventional; unless otherwise specified, the materials used in the following examples are all new materials purchased from the market.
[0026] Example 1: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10g of bamboo pulverized to the micron level and 0.5g of asphalt and add them to a three-dimensional mixer. Mix for 5 hours at a speed of 400 rpm to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 2°C for 1 minute. -1 The material was heated to 350°C at a heating rate of 30°C and calcined for 3 hours to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 5 °C·min.-1 The temperature was increased to 700℃ and calcined for 4 hours at a heating rate of 5℃·min. -1 The material was heated to 1400 °C and calcined for 4 hours at a heating rate to obtain a high-temperature carbonized material. S4. Weigh 2g of the high-temperature carbonized material obtained in S3 and add 0.15g of glucose into a three-dimensional mixer. Mix for 5 hours at a speed of 400rpm to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 2℃·min. -1 The material was heated to 400℃ and calcined for 3 hours at a heating rate of 100℃ to obtain a hard carbon anode material.
[0027] Example 2: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10 g of Reed pulverizer ground to micron level and 1 g of asphalt and add them to a three-dimensional mixer. Mix for 4 hours at a speed of 300 rpm to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 2°C / min. -1 The material was heated to 300℃ at a heating rate and calcined for 2 hours to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 5°C / min. -1 Heating to 600℃ at a heating rate of 3 h for calcination, and then heating at a rate of 5℃·min -1 The temperature was increased to 1300℃ and calcined for 3 hours to obtain high-temperature carbonized material; S4. Weigh 2g of the high-temperature carbonized material obtained in S3 and add 0.1g of sucrose into a three-dimensional mixer and mix for 4 hours at a speed of 300rpm to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 2℃·min. -1 The material was heated to 300℃ and calcined for 2 hours at a heating rate of 100℃ to obtain a hard carbon anode material.
[0028] Example 3: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10 g of sugarcane bagasse pulverized to the micron level and 0.1 g of epoxy resin and add them to a three-dimensional mixer. Mix at 500 rpm for 6 hours to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 3°C / min. -1 The material was heated to 400℃ at a heating rate and calcined for 4 hours to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 6°C / min. -1 Heating to 800℃ at a heating rate of 5 h and then calcining at 6℃·min -1 The temperature was increased to 150,000℃ and calcined for 5 hours to obtain high-temperature carbonized material; S4. Weigh 2g of the high-temperature carbonized material obtained in S3 and add 0.2g of chitosan into a three-dimensional mixer. Mix for 6 hours at a speed of 500rpm to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 3°C / min. -1 The material was heated to 500℃ and calcined for 4 hours at a heating rate of 100℃ to obtain a hard carbon anode material.
[0029] Example 4: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10g of corn cob pulverized to the micron level and 0.5g of polyethylene and add them to a three-dimensional mixer. Mix at 400rpm for 6 hours to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 2°C / min. -1 The material was heated to 400℃ at a heating rate and calcined for 2 hours to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 5°C / min. -1 Heating to 700℃ at a heating rate of 100℃ for 4 hours, then calcining at 5℃·min -1 The temperature was increased to 1400℃ and calcined for 4 hours to obtain high-temperature carbonized material; S4. Weigh 2g of the high-temperature carbonized material obtained in S3 and add 0.16g of glucose into a three-dimensional mixer. Mix at 300 rpm for 4 hours to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 2℃·min. -1 The material was heated to 400 °C and calcined for 3 hours at a heating rate of 100 °C to obtain a hard carbon anode material.
[0030] Example 5: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10g of peanut shells crushed to the micron level and 0.5g of asphalt and add them to a three-dimensional mixer. Mix for 6 hours at a speed of 500rpm to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 2°C / min.-1 The material was heated to 350 °C at a heating rate of 4 h and calcined to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 5°C / min. -1 Heating to 800℃ at a heating rate of 100℃ for 3 hours, then calcining at 5℃·min -1 The temperature was increased to 1300℃ and calcined for 5 hours to obtain high-temperature carbonized material; S4. Weigh 2g of the high-temperature carbonized material obtained in S3 and add 0.1g of sucrose into a three-dimensional mixer and mix for 4 hours at a speed of 500rpm to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 2℃·min. -1 The material was heated to 400℃ and calcined for 4 hours at a heating rate of 100℃ to obtain a hard carbon anode material.
[0031] Example 6: A method for preparing a biomass-based hard carbon anode material includes the following steps: S1. Weigh 10 g of walnut shells crushed to the micron level and 1 g of epoxy resin and add them to a three-dimensional mixer. Mix for 6 hours at a speed of 300 rpm to obtain the precursor mixture. S2. In an air atmosphere, the precursor mixture obtained in S1 is placed in a muffle furnace and heated at 2°C / min. -1 The material was heated to 400℃ at a heating rate and calcined for 3 hours to obtain a pre-oxidized material. S3. In a nitrogen atmosphere, the pre-oxidized material obtained in S2 is heated in a tube furnace at 6°C / min. -1 Heating to 700℃ at a heating rate of 100℃ for 3 hours, then calcining at 5℃·min -1 The temperature was increased to 1300℃ and calcined for 5 hours to obtain high-temperature carbonized material; S4. Weigh 2g of the high-temperature carbonized material obtained in S2 and add 0.14g of chitosan into a three-dimensional mixer. Mix for 4 hours at a speed of 500rpm to obtain the coating material. S5. In a nitrogen atmosphere, the coating material obtained in S4 is heated in a tube furnace at 3°C / min. -1 The material was heated to 350℃ and calcined for 4 hours at a heating rate of 100°C to obtain a hard carbon anode material.
[0032] Comparative Example 1: The difference from Example 1 is that the crosslinking agent in S1 is replaced with benzoic acid instead of asphalt, and the coating agent in S4 is replaced with alumina instead of glucose.
[0033] Comparative Example 2: The difference from Example 1 is that the crosslinking agent in S1 is replaced with benzoic acid instead of asphalt.
[0034] Comparative Example 3: The difference from Example 1 is that the coating agent in S4 is replaced with aluminum oxide instead of glucose.
[0035] Obviously, the above comparative examples and embodiments are only a part of the comparative examples and embodiments of the present invention, and they, along with the comparative examples and embodiments referenced based on such examples, are all within the scope of protection of this invention.
[0036] Preparation of negative electrode sheet: The hard carbon material prepared in the example was mixed with carboxymethyl cellulose (mass ratio of 95%:5%) to form a uniform slurry, coated on copper foil, dried at 60 ℃ for 12 h, and then cut into negative electrode sheets with a diameter of 10 mm for experimental batteries using a cutting machine.
[0037] Preparation of positive electrode sheet: Sodium vanadium phosphate, polyvinylidene fluoride and acetylene black (mass ratio of 80%:10%:10%) were mixed into a uniform slurry, coated on aluminum foil, dried at 60 ℃ for 12 h, and then cut into positive electrode sheets with a diameter of 12 mm for experimental batteries using a cutting machine.
[0038] Battery assembly: Hard carbon material was used as the negative electrode; sodium vanadium phosphate as the positive electrode; the electrolyte was 1M NaPF6 in ethylene glycol dimethyl ether; the separator was a glass fiber separator GF / D1823-090; the assembly sequence was as follows: negative electrode shell, negative electrode sheet, separator, positive electrode sheet, gasket, spring sheet, positive electrode shell, assembled into a coin cell in a glove box filled with an inert atmosphere. Charge-discharge cycle tests were performed on this coin cell: the charge-discharge cutoff voltage was 0.01-2V, and the charge-discharge current density was 20 mA·g. -1 .
[0039] The following tests were conducted on the battery materials assembled using the high-rate, high-efficiency biomass-based hard carbon anode material prepared in the examples. First, the compaction of the anode material, as well as its specific capacity and initial coulombic efficiency during the first charge, were tested. The test results are detailed in Table 1 and... Figure 1-2 :
[0040] The test results above show that, compared with the comparative example, the biomass-based hard carbon anode material of the present invention has a larger compaction, which ensures that the sodium-ion battery has a greater energy density, cycle life and rate performance. Secondly, it ensures balanced product performance, and the first charge specific capacity and first coulombic efficiency are improved at the same time. Although the comparative example 3 has a higher first charge specific capacity, its first coulombic efficiency is the lowest. Therefore, it can fully prove that the technical effect of the present invention is excellent.
[0041] Next, the initial charge-discharge curves of the hard carbon materials used as the negative electrodes of sodium-ion half-cells in Examples 1 and 1-3 were measured, as well as the charge-discharge curves of the hard carbon materials used as the negative electrodes of sodium-ion half-cells in Examples 1 and 1-3 at 150 mA·g. -1 Cycling performance under current density for 100 cycles, test results are detailed in [link to relevant documentation]. Figure 3 and Figure 4 ,pass Figure 3 and Figure 4 The experimental results show that the charging capacity of Example 1 is much higher than that of Comparative Examples 1-3. After 100 cycles, the charging capacity of Example 1 did not decrease, while the charging capacity of Comparative Examples 1-3 was low and the charging capacity decreased significantly after cycling. The performance of the battery of the present invention is far superior to that of Comparative Examples 1-3.
[0042] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
[0043] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a biomass-based hard carbon anode material, characterized in that, Includes the following steps: S1. Weigh the precursor and crosslinking agent and add them to a three-dimensional mixer. Mix them to obtain a precursor mixture. The precursor is a biomass raw material with a cellulose content of more than 35%, and the crosslinking agent is a petroleum-based organic waste. S2. Place the precursor mixture obtained in S1 in a muffle furnace and calcine it to obtain a pre-oxidized material. S3. The pre-oxidized material obtained in S2 is calcined in a tube furnace to obtain a high-temperature carbonized material. S4. Weigh the high-temperature carbonized material obtained in S2 and the coating agent, add them to a three-dimensional mixer, mix them, and obtain the coating material. The coating agent is a polysaccharide. S5. The coating material obtained in S4 is calcined in a tube furnace to obtain a hard carbon anode material with high rate of return and high first-time efficiency.
2. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The precursor is one or more of bamboo, reed, sugarcane bagasse, corn cob, peanut shell, and walnut shell, and the crosslinking agent is one or more of asphalt, polyethylene, and epoxy resin. The mass ratio of the precursor to the crosslinking agent is 1:0.01-0.
1.
3. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The mixing speed in step S1 is 300-500 rpm, and the mixing time is 4-6 h.
4. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The calcination atmosphere in step S2 is air, and the heating rate is 1-3℃·min. -1 The calcination temperature is 300-400℃ and the calcination time is 2-4h.
5. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The calcination atmosphere in step S3 is a nitrogen atmosphere. The calcination is divided into two steps with a heating rate of 4-6℃·min-1. The calcination temperature in the first step is 600-800℃ and the calcination time is 3-5h. The calcination temperature in the second step is 1300-1500℃ and the calcination time is 3-5h.
6. The method for preparing the biomass-based hard carbon anode material according to claim 5, characterized in that, In step S4, the coating agent is one or more of glucose, sucrose, and chitosan.
7. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, In step S4, the mass ratio of high-temperature carbonized material to coating agent is 1:0.05-0.1, the mixing speed is 300-500 rpm, and the mixing time is 4-6 h.
8. The method for preparing biomass-based hard carbon anode material according to claim 1, characterized in that, The calcination atmosphere described in step S5 is a nitrogen atmosphere, and the heating rate is 1-3℃·min. -1 The calcination temperature is 300-500℃ and the calcination time is 2-4h.
9. A biomass-based hard carbon anode material, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The application of the hard carbon anode material prepared by the method of preparing biomass-based hard carbon anode material according to any one of claims 1-8, or the application of the biomass-based hard carbon anode material according to claim 9, in the anode material of sodium-ion batteries.
